2010
DOI: 10.1097/gme.0b013e3181b82fb4
|View full text |Cite
|
Sign up to set email alerts
|

Hormone therapy and intraocular pressure in nonglaucomatous eyes

Abstract: Our study showed that IOP was significantly lower in women taking HT than in those who had never taken HT, even after removing other possible influences on IOP. The IOP-lowering effect of HT deserves further investigation to explore whether it may represent a possible new therapeutic modality for glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 17 publications
(15 reference statements)
0
33
3
Order By: Relevance
“…Additionally, PMH use may help reduce the risk for POAG (18). Clinical studies have shown hormone therapy supplementation to be associated with modest reduction in IOP as well as some evidence supporting a potential protective effect on RGCs (4, 1924). …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, PMH use may help reduce the risk for POAG (18). Clinical studies have shown hormone therapy supplementation to be associated with modest reduction in IOP as well as some evidence supporting a potential protective effect on RGCs (4, 1924). …”
Section: Discussionmentioning
confidence: 99%
“…Some report no effect of hormone therapy on IOP (Guaschino et al 2003, Abramov et al 2005, and one study (Khurana et al 2006) found that HRT raises IOP in postmenopausal females with dry eye syndrome. However, most studies observed that hormone therapy significantly lowers IOP in menopausal (Sator et al 1998) and postmenopausal women (Guaschino et al 2003, Altintas et al 2004, Uncu et al 2006, Tint et al 2010, Coksuer et al 2011; data given in Table 1). This conclusion is supported by animal models, where it has been reported that E 2 prevents retinal ganglion cell loss induced by acute IOP elevation in rats (Russo et al 2008).…”
Section: Eye Disease and The Retinamentioning
confidence: 99%
“…22 A consequence of this is raised IOP within the eye, as demonstrated by a study of postmenopausal women which found that IOP in women on hormone replacement therapy was 1.41 mmHg lower than in those not on hormone replacement therapy. 23 This rise in IOP, combined with increased susceptibility of the optic nerve resulting from the absence of circulating estrogens, may contribute to the development of glaucoma in post-menopausal women.…”
Section: Discussionmentioning
confidence: 99%